Remote Postconditioning Attenuates Ischemia/Reperfusion Injury in Rat Skeletal Muscle through Mitochondrial ATP-Sensitive K+ Channel–Dependent Mechanism - Lee, Jung Il; Wook Nha, Kyung; Suh, Jin Soo; Choo, Suk Kyu; Park, Jung Ho; Park, Jong Woong (Journal of Reconstructive Microsurgery, 2013)
The authors investigated whether a remote postconditioning (remote post-con) procedure attenuated skeletal muscle ischemia/reperfusion (I/R) injury. We determined the optimal protocol of remote post-con and investigated its mechanism. Ischemia was induced for 3 hours in rat left hindlimb and three protocols of remote post-con were applied in right hindlimb just before the end of ischemia. The first (10-second group) involved two cycles of 10 seconds of occlusion followed by 10 seconds of reperfusion. The second (5-minute group) involved two cycles of 5 minutes of occlusion/reperfusion. The third (10-minute group) involved two cycles of 10 minutes of occlusion/reperfusion. In 5- and 10-minute groups, wet/dry ratio and muscle fiber edema were significantly lower than control group. Muscle contractility was preserved in 5- and 10-minute groups. An injection of 5-hydroxydecanoate (a specific blocker of mitochondrial ATP-sensitive K+ [mKATP] channels) impaired this effect. This study demonstrates that remote post-con preserves muscle contractility and reduces tissue edema and necrosis, possibly through the activation of mKATP channels. We suggest that two cycles of 5 minutes of occlusion followed by 5 minutes of reperfusion are optimal protocols of remote post-con in skeletal muscle I/R injury.
Keywords: Ischemia/reperfusion injury; postconditioning; remote postconditioning; ATP-sensitive K+ channel